2017
DOI: 10.1636/joa-s-16-070.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the chemo-textural familiarity hypothesis for scorpion navigation

Abstract: The navigation by scene familiarity hypothesis provides broad explanatory power for how bees and ants navigate from the hive to distant food sources and back. The premise is that the visual world is decomposed into pixclaled matrices of information that are stored and readdressed as the insects retrace learned routes. Innate behaviors in these insects (including learning walks/flights and path integration) provide the important goal-directed views to allow the initial retracing (i.e., the insect must learn the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation. 66 June 10, 2020 5/34Navigation by familiarity with a local sensor 67In this paper, we consider the hypothesis that the dense fields of peg sensilla on pectines 68 are analogous to the tightly packed ommatidia in compound eyes, detecting matrices of 69 chemical and textural information that are used for navigation by familiarity.…”
supporting
confidence: 56%
“…The hypothesis appears congruent with 61 numerous behavioral observations [29][30][31][32][33][34][35][36]. Furthermore, there are now robots and 62 simulated agents that navigate autonomously via familiarity [1,18,[37][38][39], and some 63 studies [40, 41] have suggested how neural tissue, such as the central complex and 64 mushroom bodies [42-51], might be organized to accommodate familiarity-based 65 navigation. 66 June 10, 2020 5/34Navigation by familiarity with a local sensor 67In this paper, we consider the hypothesis that the dense fields of peg sensilla on pectines 68 are analogous to the tightly packed ommatidia in compound eyes, detecting matrices of 69 chemical and textural information that are used for navigation by familiarity.…”
supporting
confidence: 56%
“…Finally, although we did not detect a statistically significant difference between group means, the small differences we observed may still have biological relevance. If gaining just one additional mechanosensor can (at least) double a female’s tactile discriminatory power (Gaffin and Brayfield 2017), then females in a population with a seemingly minor upward shift in sensilla number could gain a remarkable increase in their ability to detect and avoid mating with heterospecifics. Similarly, it is difficult to determine the features of sensilla density distributions that may influence female preference solely by conducting statistical tests between KDEs.…”
Section: Discussionmentioning
confidence: 99%
“…A female that possesses just one additional sensillum would be able to distinguish among roughly twice as many patterns (2 26 = 6.7 × 10 7 ). Should individual sensilla respond to quantitative variation in touch (rather than a binary response), this would dramatically increase the number of response states and therefore further enhance tactile acuity (Gaffin and Brayfield 2017). Female damselfly thoracic sensilla thus present an external, quantifiable phenotype to investigate the mechanistic basis of tactile stimuli and female mating decisions.…”
mentioning
confidence: 99%
“…About pectines, Pocock (1893) wrote: "it is highly probable that they are useful organs of touch .... enabling their possessor to learn the nature of the surface over which it is walking". More recently, Gaffin & Brayfield (2017) hypothesized that scorpion navigation is guided primarily by tactile and olfactory cues associated with the substrate. They suggested that information about the physical texture and spatial patterns of substrate-bound chemical stimuli is captured when pectinal combs are swept over the substrate.…”
Section: Pectinal Tooth Count (Ptc) As An Ecomorphotypic Charactermentioning
confidence: 99%